Bunuel wrote:

Official Solution:

Statement (1) by itself is sufficient. From S1 it follows that \(a + b - c\) is an integer. Thus, \(2(a + b - c)\) is an even integer.

Statement (2) by itself is insufficient. Consider \(a = b = c = 0\) (the answer is "no") and \(a = 1.25\), \(c = -1.25\), \(b = 0\) (the answer is "yes").

Answer: A

I understand why answer is D but can't understand why in explanation used such example: \(a = 1.25\), \(c = -1.25\), \(b = 0\) is (the answer is "yes")

We have question "Is \(2(a+b−c)\) an odd?"

let's put this numbers in the question and we receive: \(2(1.25+0-1.25) = 0 = even\)

I think correct example will be \(a = \frac{1}{4}\) \(b = \frac{1}{4}\) and \(c =0\)

\(b = a - c\) :

\(\frac{1}{4} = \frac{1}{4} - 0\)

and \(2(a+b−c)\):

\(2(\frac{1}{4}+\frac{1}{4}-0) = 1 = odd\)

Am I miss something or this is misprint in explanation?

If \(a = 1.25\), \(c = -1.25\), \(b = 0\), then \(2(a + b - c) = 2(1.25+0 -(-1.25)) = 2*2.5=5\), not 0.